PERAN HUMAS PEMERINTAH DAERAH DALAM KASUS PENAMBANGAN PASIR BESI DI KABUPATEN KULON PROGO - Harry Broto Widodo; Siti Fatonah; Retno Hendariningrum (Jurnal Ilmu Komunikasi, 2009)
Today, Kulon Progo Regency still face the pro and con problems regarding iron sand mining. The government of Kulon Progo Regency is required to be able to build communication with all parties in solving the problems. This research is aimed at identifying the implementation of public relations role of the government of Kulon Progo Regency in facing iron sand mining case problems in Kulon Progo Regency as well as obstacles faced by the government of Kulon Progo Regency in enacting the role of public relations in dealing with the problems. This research employs qualitative descriptive analysis. The activity of qualitative descriptive analysis is done by processing the data obtained through interview, observation and documentation technique. Based on research results, it is concluded that although Public relations have done its role in the plan socialization of iron sand mining in Kulon Progo Regency, but the false perception held by the society about mining process has not changed yet, it means that the Power Control Theory which is conducted by the Public Relations Of Kulon Progo Local Government is not maximum yet. The obstacles faced by the Public Relations Of Kulon Progo Local Government in dealing with iron sand mining problems in Kulon Progo are first, internal obstacles in the function of public relations which has the position as the dominant coalition in relation to its authority in entering social responsibility, public understanding or two-way communication is not maximum yet, second, a false perception held by the people of southern sea shore upon the process of mining process.